How access to addictive drugs affects the supply of substance abuse treatment: Evidence from Medicare Part D. (23rd May 2022) - Knowles, Matthew T.
Abstract: This paper documents how substance abuse treatment (SAT) providers and services respond to increases in population‐level opioid addiction. I do this by exploiting the implementation of Medicare Part D as an exogenous increase in the availability of prescription opioids. Starting in 2006, states with higher shares of the population eligible for Medicare Part D experienced increases in residential and hospital inpatient SAT facilities, beds dedicated to SAT, and SAT facilities offering medication‐assisted treatment, relative to states with lower shares. These results suggest that the supply of SAT in the United States is capable of responding significantly to changes in demand.